2021
DOI: 10.1177/23259671211027855
|View full text |Cite
|
Sign up to set email alerts
|

Acute Versus Delayed Surgical Intervention in Multiligament Knee Injuries: A Systematic Review

Abstract: Background: The optimal timing of surgical intervention for multiligament knee injuries remains controversial. Purpose: To review the clinical and functional outcomes after acute and delayed surgical intervention for multiligament knee injuries. Study Design: Systematic review; Level of evidence, 4. Methods: We performed a search of the PubMed, Embase, Cochrane Library, and Web of Science databases from inception to September 2020. Eligible studies reported on knee dislocations, multiligament knee injuries, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 62 publications
2
18
0
1
Order By: Relevance
“…Several recent systematic reviews assessing MLKI define the term specifically as ‘disruption of at least two of the four major knee ligaments, comprising the ACL, PCL, MCL (and PMC) and LCL (and PLC)’ 1 4 15 23. Numerous original research studies and systematic reviews do not explicitly define their interpretation of MLKI, or do not define their interpretation of the ‘four primary knee ligaments’ 24–30. One recent systematic review defined MLKI as ‘three or more ligaments injured and/or knee dislocation’ 31.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent systematic reviews assessing MLKI define the term specifically as ‘disruption of at least two of the four major knee ligaments, comprising the ACL, PCL, MCL (and PMC) and LCL (and PLC)’ 1 4 15 23. Numerous original research studies and systematic reviews do not explicitly define their interpretation of MLKI, or do not define their interpretation of the ‘four primary knee ligaments’ 24–30. One recent systematic review defined MLKI as ‘three or more ligaments injured and/or knee dislocation’ 31.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, only 5/15 studies (33%) comprised original research assessing early versus delayed surgery. There is consensus for the demarcation in time point between ‘early’ and ‘late’ surgery for MLKI1 23 25 90–94; early being <3 weeks and late being >3 weeks; however, the evidence for this demarcation is unclear. Levy et al 1 noted that 3 weeks had been considered a critical time period following injury, when tissue planes can be identified and are of sufficient integrity to allow reapproximation and suture placement.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review by Mardeer et al concluded that no clear difference was observed in outcomes in acute versus delayed surgical intervention. 34 Liow et al 35 4 Both prior studies found no cases of PA damage in KDI or KDII injuries. Classically, posterior and anterior dislocations are thought to directly compress and stretch the PA, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…A systematic review by Mardeer et al concluded that no clear difference was observed in outcomes in acute versus delayed surgical intervention. 34 Liow et al 35 found that early surgical intervention within two weeks of presentation was superior to delayed treatment in multiligament knee injuries. Emergent open reduction is conducted in cases of known vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…In their meta-analysis, Mook et al [ 16 ] noted that patients undergoing acute surgery had more flexion deficits. However, a more recent meta-analysis involving 2,585 patients showed no difference in clinical and functional outcomes when comparing acute and delayed surgical intervention [ 18 ]. In our study, there were no cases of knee stiffness needing manipulation under anesthesia or arthroscopic adhesiolysis.…”
Section: Discussionmentioning
confidence: 99%